Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Certainly! Let's explore the process step-by-step for restricting the domain of the function [tex]\( f(x) = (x + 4)^2 - 6 \)[/tex] and finding its inverse for each restricted domain.
### Step 1: Understanding the Function
We start with the function:
[tex]\[ f(x) = (x + 4)^2 - 6 \][/tex]
This is a quadratic function, which is not one-to-one because it is symmetric around its vertex. To find the inverse, we need to restrict the domain so that it becomes one-to-one.
### Step 2: Finding the Inverse for Different Domains
#### 1. Restricted Domain: [tex]\( x \leq -4 \)[/tex]
First, we need to restrict the domain to [tex]\( x \leq -4 \)[/tex] to make the function one-to-one on this interval.
1. [tex]\[ x \leq -4 \][/tex]
2. Solve for the inverse:
[tex]\[ y = (x + 4)^2 - 6 \][/tex]
First, solve for [tex]\(x\)[/tex]:
[tex]\[ y + 6 = (x + 4)^2 \][/tex]
[tex]\[ \sqrt{y + 6} = x + 4 \][/tex]
Since [tex]\( x \leq -4 \)[/tex], we take the negative square root to solve for [tex]\(x\)[/tex]:
[tex]\[ x = -\sqrt{y + 6} - 4 \][/tex]
3. Therefore, the inverse function is:
[tex]\[ f^{-1}(x) = -\sqrt{x + 6} - 4 \text{ for } x \leq -4 \][/tex]
#### 2. Restricted Domain: [tex]\( x \geq -4 \)[/tex]
Second, we need to restrict the domain to [tex]\( x \geq -4 \)[/tex] to make the function one-to-one on this interval.
1. [tex]\[ x \geq -4 \][/tex]
2. Solve for the inverse:
[tex]\[ y = (x + 4)^2 - 6 \][/tex]
First, solve for [tex]\(x\)[/tex]:
[tex]\[ y + 6 = (x + 4)^2 \][/tex]
[tex]\[ \sqrt{y + 6} = x + 4 \][/tex]
Since [tex]\( x \geq -4 \)[/tex], we take the positive square root to solve for [tex]\(x\)[/tex]:
[tex]\[ x = \sqrt{y + 6} - 4 \][/tex]
3. Therefore, the inverse function is:
[tex]\[ f^{-1}(x) = \sqrt{x + 6} - 4 \text{ for } x \geq -4 \][/tex]
#### 3. Restricted Domain: [tex]\( x \leq 4 \)[/tex]
Third, we need to restrict the domain to [tex]\( x \leq 4 \)[/tex] to make the function one-to-one on this interval.
1. [tex]\[ x \leq 4 \][/tex]
2. Solve for the inverse:
[tex]\[ y = (x + 4)^2 - 6 \][/tex]
First, solve for [tex]\(x\)[/tex]:
[tex]\[ y + 6 = (x + 4)^2 \][/tex]
[tex]\[ \sqrt{y + 6} = x + 4 \][/tex]
Since [tex]\( x \leq 4 \)[/tex], we take the square root to solve for [tex]\(x\)[/tex]:
[tex]\[ x = \sqrt{y - 4} + 6 \][/tex]
3. Therefore, the inverse function is:
[tex]\[ f^{-1}(x) = \sqrt{x - 4} + 6 \text{ for } x \leq 4 \][/tex]
#### 4. Restricted Domain: [tex]\( x \geq -6 \)[/tex]
Finally, we need to restrict the domain to [tex]\( x \geq -6 \)[/tex] to make the function one-to-one on this interval.
1. [tex]\[ x \geq -6 \][/tex]
2. Solve for the inverse:
[tex]\[ y = (x + 4)^2 - 6 \][/tex]
First, solve for [tex]\(x\)[/tex]:
[tex]\[ y + 6 = (x + 4)^2 \][/tex]
[tex]\[ \sqrt{y + 6} = x + 4 \][/tex]
Since [tex]\( x \geq -6 \)[/tex], we again take the positive square root to solve for [tex]\(x\)[/tex]:
[tex]\[ x = \sqrt{y + 6} - 4 \][/tex]
3. Therefore, the inverse function is:
[tex]\[ f^{-1}(x) = \sqrt{x + 6} - 4 \text{ for } x \geq -6 \][/tex]
### Summary:
1. Restricted domain [tex]\( x \leq -4 \)[/tex]: [tex]\( f^{-1}(x) = -\sqrt{x+6} - 4 \)[/tex]
2. Restricted domain [tex]\( x \geq -4 \)[/tex]: [tex]\( f^{-1}(x) = \sqrt{x+6} - 4 \)[/tex]
3. Restricted domain [tex]\( x \leq 4 \)[/tex]: [tex]\( f^{-1}(x) = \sqrt{x-4} + 6 \)[/tex]
4. Restricted domain [tex]\( x \geq -6 \)[/tex]: [tex]\( f^{-1}(x) = \sqrt{x+6} - 4 \)[/tex]
These are the appropriate inverses for the function [tex]\( f(x) = (x + 4)^2 - 6 \)[/tex] given the specified restricted domains.
### Step 1: Understanding the Function
We start with the function:
[tex]\[ f(x) = (x + 4)^2 - 6 \][/tex]
This is a quadratic function, which is not one-to-one because it is symmetric around its vertex. To find the inverse, we need to restrict the domain so that it becomes one-to-one.
### Step 2: Finding the Inverse for Different Domains
#### 1. Restricted Domain: [tex]\( x \leq -4 \)[/tex]
First, we need to restrict the domain to [tex]\( x \leq -4 \)[/tex] to make the function one-to-one on this interval.
1. [tex]\[ x \leq -4 \][/tex]
2. Solve for the inverse:
[tex]\[ y = (x + 4)^2 - 6 \][/tex]
First, solve for [tex]\(x\)[/tex]:
[tex]\[ y + 6 = (x + 4)^2 \][/tex]
[tex]\[ \sqrt{y + 6} = x + 4 \][/tex]
Since [tex]\( x \leq -4 \)[/tex], we take the negative square root to solve for [tex]\(x\)[/tex]:
[tex]\[ x = -\sqrt{y + 6} - 4 \][/tex]
3. Therefore, the inverse function is:
[tex]\[ f^{-1}(x) = -\sqrt{x + 6} - 4 \text{ for } x \leq -4 \][/tex]
#### 2. Restricted Domain: [tex]\( x \geq -4 \)[/tex]
Second, we need to restrict the domain to [tex]\( x \geq -4 \)[/tex] to make the function one-to-one on this interval.
1. [tex]\[ x \geq -4 \][/tex]
2. Solve for the inverse:
[tex]\[ y = (x + 4)^2 - 6 \][/tex]
First, solve for [tex]\(x\)[/tex]:
[tex]\[ y + 6 = (x + 4)^2 \][/tex]
[tex]\[ \sqrt{y + 6} = x + 4 \][/tex]
Since [tex]\( x \geq -4 \)[/tex], we take the positive square root to solve for [tex]\(x\)[/tex]:
[tex]\[ x = \sqrt{y + 6} - 4 \][/tex]
3. Therefore, the inverse function is:
[tex]\[ f^{-1}(x) = \sqrt{x + 6} - 4 \text{ for } x \geq -4 \][/tex]
#### 3. Restricted Domain: [tex]\( x \leq 4 \)[/tex]
Third, we need to restrict the domain to [tex]\( x \leq 4 \)[/tex] to make the function one-to-one on this interval.
1. [tex]\[ x \leq 4 \][/tex]
2. Solve for the inverse:
[tex]\[ y = (x + 4)^2 - 6 \][/tex]
First, solve for [tex]\(x\)[/tex]:
[tex]\[ y + 6 = (x + 4)^2 \][/tex]
[tex]\[ \sqrt{y + 6} = x + 4 \][/tex]
Since [tex]\( x \leq 4 \)[/tex], we take the square root to solve for [tex]\(x\)[/tex]:
[tex]\[ x = \sqrt{y - 4} + 6 \][/tex]
3. Therefore, the inverse function is:
[tex]\[ f^{-1}(x) = \sqrt{x - 4} + 6 \text{ for } x \leq 4 \][/tex]
#### 4. Restricted Domain: [tex]\( x \geq -6 \)[/tex]
Finally, we need to restrict the domain to [tex]\( x \geq -6 \)[/tex] to make the function one-to-one on this interval.
1. [tex]\[ x \geq -6 \][/tex]
2. Solve for the inverse:
[tex]\[ y = (x + 4)^2 - 6 \][/tex]
First, solve for [tex]\(x\)[/tex]:
[tex]\[ y + 6 = (x + 4)^2 \][/tex]
[tex]\[ \sqrt{y + 6} = x + 4 \][/tex]
Since [tex]\( x \geq -6 \)[/tex], we again take the positive square root to solve for [tex]\(x\)[/tex]:
[tex]\[ x = \sqrt{y + 6} - 4 \][/tex]
3. Therefore, the inverse function is:
[tex]\[ f^{-1}(x) = \sqrt{x + 6} - 4 \text{ for } x \geq -6 \][/tex]
### Summary:
1. Restricted domain [tex]\( x \leq -4 \)[/tex]: [tex]\( f^{-1}(x) = -\sqrt{x+6} - 4 \)[/tex]
2. Restricted domain [tex]\( x \geq -4 \)[/tex]: [tex]\( f^{-1}(x) = \sqrt{x+6} - 4 \)[/tex]
3. Restricted domain [tex]\( x \leq 4 \)[/tex]: [tex]\( f^{-1}(x) = \sqrt{x-4} + 6 \)[/tex]
4. Restricted domain [tex]\( x \geq -6 \)[/tex]: [tex]\( f^{-1}(x) = \sqrt{x+6} - 4 \)[/tex]
These are the appropriate inverses for the function [tex]\( f(x) = (x + 4)^2 - 6 \)[/tex] given the specified restricted domains.
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.